2014
DOI: 10.1097/inf.0000000000000332
|View full text |Cite
|
Sign up to set email alerts
|

Measles Seropositivity in HIV-infected Kenyan Children on Antiretroviral Therapy

Abstract: This paper describes results from a cross-sectional study among HIV-infected children 15 months to 12 years of age who were receiving antiretroviral therapy. We found a low prevalence of measles IgG seropositivity (45.7%) and identified CD4% ≥ 25 as a predictor. Most HIV-infected children on ART were not measles seropositive and might benefit from revaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
0
9
1
Order By: Relevance
“…Cohort and caregiver characteristics, as well as measles serostatus before revaccination were previously described 13 . Of the enrolled children, 220 (95%) attended their one month post revaccination visit, 224 (97%) attended their 12 month visit, and 220 (95%) attended their 24 months visit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cohort and caregiver characteristics, as well as measles serostatus before revaccination were previously described 13 . Of the enrolled children, 220 (95%) attended their one month post revaccination visit, 224 (97%) attended their 12 month visit, and 220 (95%) attended their 24 months visit.…”
Section: Resultsmentioning
confidence: 99%
“…HIV-infected children and their caregivers were recruited from the HIV Comprehensive Care Centre at Kenyatta National Hospital in Nairobi, Kenya, during routine HIV care visits between May 2011 and January 2013, as previously described 13 . Caregivers willing to be screened were asked to read and sign an informed consent document, approved by Kenyatta National Hospital and the University of Washington.…”
Section: Methodsmentioning
confidence: 99%
“…We support the recent Paediatric European Network for Treatment of AIDS/ Children's HIV Association guidelines, 2 W e were interested to read the paper by Newman et al 1 They conclude that most HIV-infected children were not immune to measles and "might benefit from revaccination." We agree that many HIVinfected children are not immune to measles, but revaccination may only benefit a proportion of these children.…”
Section: Discussionmentioning
confidence: 83%
“…The demographic characteristics of the overall cohort have been described previously [9]. Briefly, 232 children attending routine clinic visits at the Comprehensive HIV Care Centre at Kenyatta National Hospital in Nairobi, Kenya were enrolled.…”
Section: Demographic and Clinical Characteristics Of Study Participantsmentioning
confidence: 99%
“…HIV-infected children are less capable of mounting and maintaining responses to vaccination against measles than uninfected, otherwise healthy children [4][5][6][7]. Studies in Kenya have demonstrated that administration of anti-retroviral therapy (ART) to HIV-infected individuals alone is not sufficient to restore measles antibody titres [8,9].…”
Section: Introductionmentioning
confidence: 99%